Consensus en conflict in waterbeheer: Een uitnodiging tot verdere vergelijking - Davids, Karel (TSEG - The Low Countries Journal of Social and Economic History, 2023)
Consensus en conflict. Waterbeheer in de Nederlanden 1200-1800 is an impressive book. The question is topical. Who shaped water management in the Low Countries? Is the traditional image that water management was a matter of cooperation and striving for consensus correct, or was there often a conflict of interests and conflict? The purpose of my contribution is not so much to criticize but rather to stimulate a further exchange of views on certain aspects of the book. This concerns in particular the international comparative perspective. Although Consensus and Conflict focuses on "the Netherlands" (including the Flemish coastal plain), at several points it also takes a look at areas beyond, especially France, England and Northwest Germany.